Textbook in instituto de gestión sanitaria (ingesa) - del Campo Puerta, Pilar (Revista General de Información y Documentación, 2015)
Textbooks, once they have fulfilled their function of teaching, are forgotten and their salvation depends, almost exclusively, on the appreciation and consideration of their holders; then, in most cases, some private it is collections are donated to institutions and public libraries which are kept bibliographic heritage. Instituto de Gestión Sanitaria (INGESA) is the Health Management Institute, one institution located in Madrid where textbooks of the nineteenth Century are preserved in their library. Given that many successive editions were made with changes in title, length, etc. in textbooks of that period, which adds a problem to cataloging the titles that will be analyzed belong to the list of books authorized by various Real Decrees, for students who were studying in primary and secondary education in schools and colleges.